Human Adult Fibroblast‐like Synoviocytes and Articular Chondrocytes Exhibit Prominent Overlap in Their Transcriptomic Signatures. Issue 6 (1st May 2021) - Jones, Kyle; Angelozzi, Marco; Gangishetti, Umesh; Haseeb, Abdul; de Charleroy, Charles; Lefebvre, Véronique; Bhattaram, Pallavi
Abstract : Objectives: Fibroblast‐like synoviocytes (FLS) and articular chondrocytes (AC) derive from a common pool of embryonic precursor cells. They are currently believed to engage in largely distinct differentiation programs to build synovium and articular cartilage and maintain healthy tissues throughout life. We tested this hypothesis by deeply characterizing and comparing their transcriptomic attributes. Methods: We profiled the transcriptomes of freshly isolated AC, synovium, primary FLS, and dermal fibroblasts from healthy adult humans using bulk RNA sequencing assays and downloaded published single‐cell RNA sequencing data from freshly isolated human FLS. We integrated all data to define cell‐specific signatures and validated findings with quantitative reverse transcription PCR of human samples and RNA hybridization of mouse joint sections. Results: We identified 212 AC and 168 FLS markers on the basis of exclusive or enriched expression in either cell and 294 AC/FLS markers on the basis of similar expression in both cells. AC markers included joint‐specific and pan‐cartilaginous genes. FLS and AC/FLS markers featured 37 and 55 joint‐specific genes, respectively, and 131 and 239 pan‐fibroblastic genes, respectively. These signatures included many previously unrecognized markers with potentially important joint‐specific roles. AC/FLS markers overlapped in their expression patterns among all FLS and AC subpopulations, suggesting that they fulfill joint‐specific properties in all, rather than in discrete, AC and FLS subpopulations. Conclusion: This study broadens knowledge and identifies a prominent overlap of the human adult AC and FLS transcriptomic signatures. It also provides data resources to help further decipher mechanisms underlying joint homeostasis and degeneration and to improve the quality control of tissues engineered for regenerative treatments.